Resilience and self-regulated learning as predictors of student competence gain in times of the COVID 19 pandemic – evidence from a binational sample - Imhof, Margarete; Worthington, Debra; Burger, Julian; Bellhäuser, Henrik (Frontiers in Education, 2024)
Emergency Remote Teaching (ERT) was introduced around the globe during the COVID-19 pandemic to ensure that students could continue with their studies during social distancing.Subsequent studies found considerable individual differences in the adjustment to ERT and identified resilience as a critical factor for coping with the challenges of independent studying. The growing evidence led to calls for resilience training in preparation for emergency situations. Against the backdrop of a three-phase model of self-regulated learning, this study examines self-regulated learning activities as an additional protective resource and a predictor for academic performance in ERT. Results from a survey of resilience, self-regulated learning strategies, and competence gain completed by students from universities in the US and Germany (N = 333) found self-regulated learning strategies to be more predictive of student competence gain than resilience. As a 2 This is a provisional file, not the final typeset article consequence, in addition to fostering resilience, institutions should also include self-regulation strategies in student training and support programs to better prepare students for academic success.